Economic development and the return to human capital: A smooth coefficient semiparametric approach - Mamuneas, Theofanis P.; Savvides, Andreas; Stengos, Thanasis (My University, 2006)
This paper investigates the impact of human capital on the process of economic growth by allowing the contribution of traditional inputs (capital and labour) as well as that of human capital to vary both across countries and time. The former is accomplished by constructing an index of TFP growth for traditional inputs, while the latter through semiparametric methods. We derive estimates of the output elasticity and social return to human capital for 51 countries at various stages of economic development.